Distribution and structure of the population of Abies religiosa (H.B.K.) Schl. et Cham., in the Cofre de Perote, State of Veracruz, Mexico - Sanchez-Velasquez, Lazaro Rafael; Pineda-Lopez, Ma. Del Rosario; Hernandez-Martinez, Amador (Instituto de Ecología, A.C., 1995)
Analysis of relative frequency and multiple correlations were used to determine altitude, slope, and exposure of places where Abies religiosa (H.B.K.) Schl. et Cham. Is found in the Cofre de Perote area, state of Veracruz, Mexico. This study includes a population structure analysis, as well as an analysis of the relationships between the common annual increment (CAI), the variables mentioned above and the coverage, the standing tree basal areas, and the stump basal areas. The results show that the fir forest is restricted to certain slope and altitude conditions. This is due primarily to the loss of forested land to agriculture. There is a 0.579 probability of finding fir trees at altitudes between 3200 and 3400 meters and on slopes of 40% to 55%. With respect to exposure, the NW side shows the greatest frequency (58%). A high correlation (r=-0.96) was found between the normal diameter (ND) and the age of the trees. Moreover, the age structure is that of a shade-tolerant species. Finally, a positive relationship was found between CAI, the stump basal area, and the slope (r=0.77, p<0.001).